2021
DOI: 10.9734/ijecc/2021/v11i1130535
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Validation of DSSAT CROPGRO Peanut Model for Yield and Yield Attributing Characters of Groundnut Varieties in Northern Agro-Climatic Zone of Tamil Nadu

Abstract: Aim: The research study was conducted to calibrate and validate the DSSAT CROPGRO peanut model for simulating the potential yield of groundnut to deciding the best possible management options at major growing areas of Northern Agro-Climatic zone of Tamil Nadu. Study Design:  The experiment was conducted in Split plot Design with four Sowing dates and cultivars. Methodology: The DSSAT model requires layer wise soil data (physical and chemical), including soil texture and other soil properties. Daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The validation employed one-year weather data from 2019. The genetic coefficient of the Pectomech tomato cultivar was derived using the trial-and-error method as described by Thirumeninathan et al (2021). After every trial-and-error simulation run, adjustment was made to match the observed crop phenology and yield with the simulated values.…”
Section: Parameterization Of the Dssat Cropgro Modelmentioning
confidence: 99%
“…The validation employed one-year weather data from 2019. The genetic coefficient of the Pectomech tomato cultivar was derived using the trial-and-error method as described by Thirumeninathan et al (2021). After every trial-and-error simulation run, adjustment was made to match the observed crop phenology and yield with the simulated values.…”
Section: Parameterization Of the Dssat Cropgro Modelmentioning
confidence: 99%